2002
DOI: 10.1002/1521-4184(200205)335:5<229::aid-ardp229>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antitumor Activity of Enantiomerically Pure [1, 2-Diamino-1-(4-fluorophenyl) propane]dichloroplatinum(II) Complexes

Abstract: Enantiomerically pure 1, 2‐diamino‐1‐(4‐fluorophenyl)propanes were synthesized by stereospecific and stereoselective procedures by use of the (1R, 2S)‐ and (1S, 2R)‐2‐amino‐1‐(4‐fluorophenyl)propanols (12a) as intermediates. The enantiomeric purity was determined by 1H NMR spectroscopy after conversion of the propanolamines and the diamines with (1R)‐myrtenal into mono‐ and diimines. For the coordination to platinum the diamines were reacted with K2PtCl4. The resulting dichloroplatinum(II) complexes 4F‐Ph/Me‐P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
(70 reference statements)
2
10
0
Order By: Relevance
“…[9] In an earlier study, we demonstrated the increase of in vitro cytotoxicity by the exchange of one 4-fluorophenyl residue with a methyl (4F-Ph/Me-PtCl 2 ), ethyl (4F-Ph/Et-PtCl 2 ) or propyl group (4F-Ph/ Prop-PtCl 2 ). [10][11][12] Interestingly, the C2-methyl substituent led to different cytotoxic effects of the threo isomers: S,S > R,R > S,R = R,S. [10] Elongation of the side chain in the erythro series with one or two methylene groups also produced this effect: &ok?…”
Section: Introductionmentioning
confidence: 99%
“…[9] In an earlier study, we demonstrated the increase of in vitro cytotoxicity by the exchange of one 4-fluorophenyl residue with a methyl (4F-Ph/Me-PtCl 2 ), ethyl (4F-Ph/Et-PtCl 2 ) or propyl group (4F-Ph/ Prop-PtCl 2 ). [10][11][12] Interestingly, the C2-methyl substituent led to different cytotoxic effects of the threo isomers: S,S > R,R > S,R = R,S. [10] Elongation of the side chain in the erythro series with one or two methylene groups also produced this effect: &ok?…”
Section: Introductionmentioning
confidence: 99%
“…The investigations presented in this paper continue the structure activity relationship study on [1,2-diamino-1-(4-fluorophenyl)ethane]dichloroplatinum(II) complexes [16,17] The 4F-Ph-PtCl 2 complexes are cisplatin derivatives with high selectivity for mammary carcinoma cells [30].…”
Section: Discussionmentioning
confidence: 56%
“…Therefore, we tried to optimize the antiproliferative activity by exchanging a 4-fluorophenyl moiety for an alkyl chain. In a previously published SAR study [16,17], we demonstrated a marginal loss of cytotoxicity for the MCF- The antitumor activity was determined, besides the asymmetric C-atoms, by the kind of leaving group. It is expected that after the transport into the cytoplasm, the platinum complexes hydrolize into the aqua-and the diaquaplatinum(II) complexes, which then bind to nucleobases [35].…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations